Recent Advances in Maintenance and Infrastructure Management - Cigolini, Roberto Davide; Deshmukh, Abhijit V.; Fedele, Lorenzo; McComb, Sara Ann (Springer London : Imprint: Springer, 2009)
Recent Advances in Maintenance and Infrastructure Management is a collection of papers highlighting the state of the art in maintenance of large structures and management of infrastructures. The papers selected in this book are written by international experts from academia and industry, and were presented during the past three International Conference on Maintenance Management (MM Conferences) held from 2005 to 2007 and organized by CNIM (Italian National Committee for Maintenance). The selected papers are categorized into four thematic areas: 1. reliability and maintenance; 2. mathematical modeling and metrics for maintenance; 3. maintenance management and organization, and; 4. facilities management and contracting. The papers cover topics ranging from embedded sensors for diagnostics of structures to organizational issues related to effective maintenance planning. Recent Advances in Maintenance and Infrastructure Management provides readers with a snapshot of the latest developments in the tools and techniques used to conduct maintenance of complex infrastructures and systems. The book will be of interest to researchers and practitioners in academia and industry involved in planning and deployment of maintenance operations. Additionally, this can serve as a reference text for advanced courses in operations management, and structural health monitoring.